Cervical length for predicting preterm birth and a comparison of ultrasonic measurement techniques - O’Hara, Sandra; Zelesco, Marilyn; Sun, Zhonghua (Minnis Journals, 2013)
Introduction: Preterm birth is the leading cause of neonatal morbidity and mortality not attributable to congenital anomalies or aneuploidy. It has been shown that a shortened cervix is a powerful indicator of preterm births in women with singleton and twin gestations – the shorter the cervical length, the higher the risk of spontaneous preterm birth. Ultrasound measurements of the cervix are a more accurate way of determining cervical length (CL) than using a digital method.Background: There are three approaches that may be used to perform ultrasound measurements of the cervix; these are the transabdominal (TA), transperineal (TP) and the transvaginal (TV) approach. The TV approach is considered to be the gold standard. In women who are considered to be at a high risk of preterm birth it is now recommended that the cervix is measured at the mid-trimester ultrasound using the TV ultrasound approach. For women considered to be at a historical low risk the TV scan is not recommended, however it has been found that many women who deliver a preterm baby have no known risk factors.Conclusion: There is contradictory evidence in the literature with regard to the correlation between TA, TP and TV measurements. This article provides an overview of these three approaches with a focus on the clinical value for the assessment of the maternal cervix.